1970
DOI: 10.1002/j.2050-0416.1970.tb03296.x
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Deficient Mutants of Bottom Brewer's Yeast. I. Frequencies and Types of Mutant in Various Strains

Abstract: Four strains of bottom brewer's yeast used in Czech breweries did not differ substantially from one another in their frequencies of spontaneous respiratorydeficient (RD) mutants as tested by the triphenyl tetrazolium chloride (TTC) overlay technique. These frequencies amounted to 1.1-1.4% of the total viable cell number after cultivation in bottom layers of wort. The strain which had the highest rate of aerobic growth gave a spontaneous mutation frequency of 0.5% in shaken cultures.In comparison with the TTC o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1970
1970
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…However, if the mutation weakens the yeast, the mutated strain will be unable to compete and will soon be outgrown by the non‐mutated yeast population. The characteristics that are routinely encountered resulting from mutation that can be harmful to a wort fermentation are: the tendency of yeast strains to mutate from flocculent to non‐flocculent ; the loss of ability to ferment maltotriose ; the presence of respiratory deficient (RD, ‘petite’) mutants .…”
Section: Genetic Stability Of Brewer's Yeast Strainsmentioning
confidence: 99%
“…However, if the mutation weakens the yeast, the mutated strain will be unable to compete and will soon be outgrown by the non‐mutated yeast population. The characteristics that are routinely encountered resulting from mutation that can be harmful to a wort fermentation are: the tendency of yeast strains to mutate from flocculent to non‐flocculent ; the loss of ability to ferment maltotriose ; the presence of respiratory deficient (RD, ‘petite’) mutants .…”
Section: Genetic Stability Of Brewer's Yeast Strainsmentioning
confidence: 99%
“…The petite condition has been reported to affect flocculence (13). Petites of C75-M24, C77-M24-23, and 169 were induced with ethidium bromide (cf.…”
Section: Flocculence Of Petitesmentioning
confidence: 99%
“…Mutation to respiratory deficiency (the petite condition) has been reported to affect the flocculence of Saccharomyces carlsbergensis strains (5,13). It has also been reported that petites of the S. cerevisiae strain 169 are nonflocculent (14).…”
Section: Influence Of Growth Conditions and Respiratory Deficiencymentioning
confidence: 99%
“…Repercussions include changes in flocculation and utilization of maltotriose (18). Yeast drift can also arise through the partial or complete loss of mitochondrial DNA, leading to the production of so-called "petites" (19)(20)(21). Although alcoholic fermentation is anaerobic, meaning there is no role for a respiratory function in mitochondria, the latter organelles do have other metabolic functions in brewery fermentations (22)(23)(24).…”
Section: Brewing Yeastmentioning
confidence: 99%